Gastronomic experience (co)creation: evidence from Taiwan and Catalonia. Issue 3 (4th May 2022) - Lin, Min-Pei; Marine-Roig, Estela; Llonch-Molina, Nayra
ABSTRACT: The design of gastronomic experiences based on consumer opinion (co-creation) can contribute to improving the online gastronomic image and the overall image of destinations. By evaluating and sharing their experience on social media, the visitor expresses different levels of satisfaction and loyalty towards the destination. This user-generated content (UGC) represents useful information for analysing the perception of gastronomic experiences and the formation of online gastronomic images. The semiotic model used here considers three semantic aspects of the gastronomic image to analyse gastronomic experiences through big data analytics. The model was applied to two regions with different gastronomic cultures: Taiwan (Asia) and Catalonia (Europe) and four types of experiences. A total of 17, 214 online travel reviews (OTRs) from 2008 to 2019 were selected from TripAdvisor's 'things to do' section, which includes various tours and gastronomic activities that are different from typical dining experiences in restaurants. The results highlight the growth of OTRs before the COVID-19 pandemic, the high satisfaction of the participants in the reviewed activities, and differences in popularity and attractiveness according to activity, category and region. The findings also showcase notable differences in destination branding and marketing strategies between the regions.